Correlation, regression and cluster analyses on yield attributes and popping characteristics of popcorn (Zea mays L. everta) in derived savanna and rainforest agro-ecologies of Nigeria - Oloruntoba Olatayo OLAKOJO (University of Ljubljana, Biotechnical Faculty, 2021)
Information on the genetic and agronomic relationship among the crop characters is important for the breeding programs. This study aimed at determining the relationship among grain yield, popping expansion and other agronomic characters in 19 popcorn lines evaluated in replicated trials at two locations. Correlation analysis was carried out to determine the relationship between agronomic traits while multiple stepwise regression analyses was used to determine the contribution of other agronomic traits to grain yield. Results showed that plant and ear heights as well as cob length exhibited positive and significant association with grain yield. Popping volume showed negative and significant association (-0.45**) with grain yield while 100-grain mass had a negative and significant correlation (-0.37**) with popping volume. Stepwise multiple regression analysis showed that ear height, cob length, plant aspect and 100-grain mass contributed a total of 53.66 % to variation in grain yield, with ear height contributing the highest portion (22.51 %). Cluster analysis grouped popcorn lines into four different clusters, where ‘Small Pearl Shaped’ and ‘Popcorn 33-1-Y’ belonged to cluster II and IV, respectively, showing how divergent they are and possible utilization for hybrid formation. Improvement for popcorn should focus on identifying lines with acceptable level of popping volume and improved on their grain yield and yield attributes.